The Distribution and Use of Box (Buxus sempervirens L.) in the Northeastern Iberian Peninsula During the Holocene. (4th March 2021) - Piqué, Raquel; Morera, Núria; Revelles, Jordi; Castells, Eva; López-Bultó, Oriol; Franch, Anna; Burjachs, Francesc
ABSTRACT: The aim of this paper is to evaluate the distribution of box ( Buxus sempervirens L . ) in the Holocene vegetation of NE Spain and its use during prehistory. The scarcity of box in pollen records contrasts with the frequent presence of box charcoal at archaeological sites in the north-eastern Iberian Peninsula. Box charcoal has been documented in 41 Holocene sites, indicating its systematic use as firewood. To date, wooden artefacts have only been documented at La Draga, an early Neolithic site (5324–4977 cal BC) located on the shore of Lake Banyoles (Spain). The abundance of B. sempervirens among the artefacts is remarkable, with 85 out of 155 objects made from this wood, including sickle handles, digging sticks, wedges, adze handles, needles, combs and other objects of unknown function. The evaluation of B. sempervirens charcoal and pollen data from different Holocene sites, and the evidence of its use for the manufacture of objects, demonstrate the importance of this species for prehistoric societies.